Cell death-based treatment of glioblastoma - Fulda, Simone (Cell Death Dis, 2018)
Cancer cells including glioblastoma have typically evolved multiple mechanisms to escape programmed cell death in order to maintain their survival. Defects in cell death mechanisms not only facilitate tumorigenesis but also ensure resistance to current anticancer therapies. This emphasizes that targeting cell death pathways may provide a means to tackle one of the Achilles’ heels of cancer. Over the last decades several approaches have been developed to selectively target cell death pathways for therapeutic purposes. Some of these concepts have already been transferred into clinical application in oncology and may open new perspectives for the treatment of cancer.